(untitled) - Burgos, Julio César (Universidad Nacional de Cuyo. Facultad de Ciencias Agrarias)

Tratamiento con ácido sulfúrico de semillas de la acacia blanca (Robinia pseudo acacia L.) cosechadas en Mendoza (1956)

(untitled)
The results obtained in germination test with seeds of "black locust" (Robinia Pseudo Acacia L) previously treated with sulphuric acid concentrated (d. 1.84) are given. Those test were made in order to get a good germination considering the water tight seed coat that those seeds have in a great percentage. The seeds were soaked in the solution for some minutes; the 180 and 210 minutes soaking (90 and 86.5 % respectively) gave the highest percentage and the fasted process of germination, which were higher than those obtained as efective by other researches. The test made would constitute another evidence of the effect of the locality of production upon the degree of water tightness of the Black locust seeds. The author suggests that the previous treatments of the seeds, the rusticity and quick growing of this species and the furrow system of irrigation so common in the zone will enable, perhaps with success the stablishment of woods of this valuable forestal species, by direct seeding.